Adult onset ornithine transcarbamylase deficiency: an unusual cause of semantic disorders. Issue 7 (16th June 2004) - Rimbaux, S; Hommet, C; Perrier, D; Cottier, J P; Legras, A; Labarthe, F; Lemarcis, L; Autret, A; Maillot, F
Abstract : Ornithine transcarbamylase deficiency (OTCD) is the most common urea cycle disorder. This condition usually presents in neonates or children. This report describes the clinical case of a 21 year old woman who was diagnosed in adulthood during the course of an unexplained coma. After recovery from the coma, she presented very unusual neuropsychological disorders involving memory and the meaning of certain words, suggesting a semantic deficit. The discovery of OTCD in adulthood is rare and the neuropsychological consequences may be unique.